Platform abstracts. (1st September 2013) - Lenherr, Sara M.; Latini, Jerilyn M.; Oldendorf, Ann L.; Quentin Clemens, J.; Cameron, Anne P.; Waters, Katarina Lesjak; Riordan, Anne L.; Flanagan, Ann; Vogel, Lawrence C.; Kelly, Erin H.; Spungen, Ann M.; Asselin, Pierre; et al.
Abstract : Objective Studies have shown that management with an indwelling catheter for patients with neurogenic bladder dysfunction (NGB) is associated with more complications that are urological but little is known about the effects on quality of life. Design A prospective cross-sectional cohort study in a tertiary care neurourology clinic. Participants/Methods Patients were defined according to bladder management: group 1 (diaper voiding, indwelling urethral, suprapubic tube, or condom catheter) or group 2 (urinate normally, clean intermittent catheterization (CIC), or stoma). Results The 158 patients (67 women and 91 men) with mean age of 42.4 years (range 18.8-75.4 years) had a mean time from neurologic insult of 15.9 years. Sixty five percent of the cohort had a traumatic spinal cord injury and the remainder had other causes for NGB (multiple sclerosis, spina bifida, and non-traumatic SCI). Thirty patients were included in group 1 and 120 in group 2. Health-Related quality of Life (HRQOL) responses were similar for both bladder management groups (SF-12, AUA Symptom Index, Incontinence Symptom Index). However, when patients were explicitly asked "In general how satisfied are you with the way your bladder is managed?" they were more satisfied if they did not have an indwelling catheter or diaper voiding ( P value 0.02). A subgroup analysis of patients using CIC (self or caregiver) showed catheterization frequency of 5.5 ± 1.8 times per day and a majority viewed CIC as easy (mean score 2.6 ± 2.1, range: 1 very easy to 10 extremely difficult). Conclusion Patients utilizing an indwelling catheter or diaper voiding were no more satisfied with their HRQOL than were those utilizing CIC or stoma to manage their bladders. When asked specifically about their bladder management, patients were significantly less satisfied with their bladder management if they were using an indwelling catheter or diaper voiding. While these results are limited by the small and self-selected cohort, these data illustrates the need for standardized validated questionnaires to assess bladder management satisfaction in the neurogenic bladder patient population.